Association of GTF2I, NFKB1, and TYK2 Regional Polymorphisms With Systemic Sclerosis in a Chinese Han Population - Liu, Chenxi; Yan, Songxin; Chen, Haizhen; Wu, Ziyan; Li, Liubing; Cheng, Linlin; Li, Haolong; Li, Yongzhe (Frontiers in Immunology, 2021)
Objectives Systemic sclerosis (SSc) is an uncommon autoimmune disease that varies with ethnicity. Single nucleotide polymorphisms (SNPs) in the GTFSI, NFKB1, and TYK2 genes have been reported to be associated with SSc in other populations and in individuals with various autoimmune diseases. This study aimed to investigate the association between these SNPs and susceptibility to SSc in a Chinese Han population. Method A case-control study was performed in 343 patients with SSc and 694 ethnically matched healthy controls. SNPs in GTF2I, NFKB1, and TYK2 were genotyped using a Sequenom MassArray iPLEX system. Association analyses were performed using PLINK v1.90 software. Result Our study demonstrated that the GTF2I rs117026326 T allele and the GTF2I rs73366469 C allele were strongly associated with patients with SSc (P = 6.97E-10 and P = 1.33E-08, respectively). Patients carrying the GTF2I rs117026326 TT genotype and the GTF2I rs73366469 CC genotype had a strongly increased risk of SSc (P = 6.25E-09 and P = 1.67E-08, respectively), and those carrying the NFKB1 rs1599961 AA genotype had a suggestively significantly increased risk of SSc (P = 0.014). Moreover, rs117026326 and rs73366469 were associated with SSc in different genetic models (additive model, dominant model, and recessive model) (P < 0.05) whereas rs1599961 was associated with SSc in the dominant genetic model but not in the addictive and recessive models (P = 0.0026). TYK2 rs2304256 was not significantly associated with SSc in this study. Conclusion GTF2I rs117026326 and rs73366469 SNPs were strongly associated with SSc in this Chinese Han population. NFKB1 rs1599961 showed a suggestive association with SSc, and no significant association was found between TYK2 rs2304256 and SSc in this Chinese Han population.